1989
DOI: 10.1111/j.1365-3032.1989.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐eclosion diuresis in adult Heliothis zea

Abstract: ABSTRACT. The marked weight loss that follows adult eclosion in Heliothis zea (Boddie) (Lepidoptera: Noctuidae) was found to be the result of diuresis. This diuretic weight loss amounted to 18.2% of the emergence weight in females and 22.5% in males. Ligation between head and thorax immediately following emergence resulted in a significant reduction in this weight loss. Injection of homogenates of brain (BR) or suboesophageal ganglion (SOG) partially restored the weight loss in ligated insects, indicating pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They presented evidence that this factor lacked DH effects on older adults, and concluded that post-feeding diuresis in the monarch butterfly is controlled by a yet undefined nervous mechanism. Recently, Bushman et al [38] using crude brain or sub-esophageal homogenates reported post adult eclosion fluid loss in vivo and in vitro in Heliothis zea.…”
Section: Discussionmentioning
confidence: 99%
“…They presented evidence that this factor lacked DH effects on older adults, and concluded that post-feeding diuresis in the monarch butterfly is controlled by a yet undefined nervous mechanism. Recently, Bushman et al [38] using crude brain or sub-esophageal homogenates reported post adult eclosion fluid loss in vivo and in vitro in Heliothis zea.…”
Section: Discussionmentioning
confidence: 99%
“…The reader who has come this far may wonder whether a dynamic paracellular pathway may be unique to gorging hematophagous insects and therefore irrelevant to other epithelia. On the contrary, the ability to commence a diuresis on short notice is also observed in phytophagous insects that gorge on the sap of plants 91 . Moreover, insects leaving their aquatic habitats with first flight undergo a so‐called eclosion diuresis that lightens the load 92 .…”
Section: Tight and Septate Junctionsmentioning
confidence: 99%
“…Neurohormonal control of post-eclosion diuresis has been demonstrated in one species of moth, Heliothis zea (Noctuidae) (Bushman et al, 1989). The aim of the present work was to investigate the extent and hormonal basis of diuresis in the flightless silkmoth Bombyx mori L.…”
mentioning
confidence: 97%